Efficient and Syntax-Compliant JPEG 2000 Encryption Preserving Original Fine Granularity of Scalability. (21st February 2008) - Yang, Yang; Zhu, Bin B.; Li, Shipeng; Yu, Nenghai
Abstract : A novel syntax-compliant encryption primitive and an efficient syntax-compliant JPEG 2000 encryption scheme are presented in this paper. The syntax-compliant encryption primitive takes, as input, syntax-compliant plaintext and produces syntax-compliant ciphertext. It is faster than all the other syntax-compliant encryption primitives we know. Our JPEG 2000 encryption scheme encrypts independently either each codeblock segment (normal mode) or each intersection of a codeblock segment and a codeblock contribution to a packet (in situ mode). Truncation-invariant parameters uniquely identifying each independently encrypted data block are combined with a global initialization vector to generate on the fly an initialization vector (IV) used to encrypt the data block. These IVs can be correctly regenerated even when the encrypted codestream is truncated. Encrypted codestreams are syntax-compliant. The original granularity of scalability is fully preserved after encryption so that an encrypted codestream can be truncated to adapt to different representations without decryption. Our JPEG 2000 encryption scheme is fast, error-resilient, and has negligible file-size overhead.